2020
DOI: 10.1016/j.chest.2020.08.975
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Clinical Outcomes and Baseline Bmi or Annualized Weight Loss in Patients With Idiopathic Pulmonary Fibrosis Enrolled in the Pulmonary Fibrosis Foundation Patient Registry

Abstract: Low baseline body mass index (BMI) and weight loss have been linked with poor outcomes in patients with idiopathic pulmonary fibrosis (IPF). This analysis investigated the association between clinical outcomes and baseline BMI or annualized change in body weight in patients with IPF enrolled in the Pulmonary Fibrosis Foundation Patient Registry (PFF-PR). METHODS: This analysis examined the relationship between (a) BMI group at enrollment (<25 kg/m2, 25 to <30 kg/m2 or $30 kg/m2) or annualized percent change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
2
0
1
Order By: Relevance
“…Moreover, the rate of SAEs over 52 weeks was also numerically greater in placebo-treated patients with >5% weight loss versus ≤5% weight loss [25], similar to the results of our post hoc analysis. However, in contrast to our findings and the findings from a real-world registry [26], the rate of mortality in the INPULSIS studies was numerically lower in placebo-treated patients with >5% weight loss versus ≤5% weight loss [25].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, the rate of SAEs over 52 weeks was also numerically greater in placebo-treated patients with >5% weight loss versus ≤5% weight loss [25], similar to the results of our post hoc analysis. However, in contrast to our findings and the findings from a real-world registry [26], the rate of mortality in the INPULSIS studies was numerically lower in placebo-treated patients with >5% weight loss versus ≤5% weight loss [25].…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings expand on results from other studies that have assessed the relationship between BMI, weight loss, and outcomes in IPF [12][13][14][25][26][27]. A single-center cohort study that used bioelectrical impedance analysis found that BMI was independently associated with mortality in IPF [27], and US registry data identified a relationship between longitudinal reductions in BMI and risk of mortality [12].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation